Schistosomal MicroRNAs Isolated From Extracellular Vesicles in Sera of Infected Patients: A New Tool for Diagnosis and Follow-up of Human Schistosomiasis. (14th November 2016) - Meningher, Tal; Lerman, Galya; Regev-Rudzki, Neta; Gold, Daniel; Ben-Dov, Iddo Z.; Sidi, Yechezkel; Avni, Dror; Schwartz, Eli
Abstract: Background: Schistosomiasis traditionally has been diagnosed by detecting eggs in stool or urine. However, the sensitivity of these examinations is limited, especially in travelers with a low worm burden. Serologic tests have a greater sensitivity, but their results remain positive regardless of treatment and thus cannot be used for follow-up of patients. We hypothesized that detection of worm microRNAs (miRNAs) in serum can overcome the drawbacks of the existing diagnostic methods. Methods and Results: Twenty-six returning travelers with schistosomiasis (based on positive results of serologic tests or detection of ova) and 17 healthy controls were included in the study. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) amplification of miRNA extracted directly from 500 µL of serum had limited sensitivity and specificity. However, qRT-PCR analysis of RNA extracted from 200 μL of serum extracellular vesicles detected 4 schistosomal miRNAs; the sensitivity and specificity of the 2 highest expressed miRNAs (bantam and miR-2c-3p) were 86% and 84%, respectively. In 7 patients with posttreatment serum available for analysis, we observed outcomes ranging from a reduction in the schistosomal miRNA level to full recovery from disease. Conclusions : qRT-PCR of pathogen miRNAs isolated from extracellular vesicles in sera from infected individuals may provide a new tool for diagnosing schistosomiasis in patients with a low parasite burden. This assay could also be used for evaluating the outcome of therapy, as well as disease-control programs.